Characterizing the Lateral Friction of Nanoparticles on On‐Chip Integrated Black Lipid Membranes. Issue 6 (23rd November 2012) - Chen, Tianhong; Reinhard, Björn M.
Abstract The use of nanoparticles (NPs) in biomedical applications creates a need for appropriate model systems to systematically investigate NP–membrane interactions under well‐defined conditions. Black lipid membranes (BLMs) are free‐floating membranes with defined composition that are ideally suited for characterizing NP–membrane interactions free of any potential perturbation through a supporting substrate. Herein, arrays of microfabricated BLMs are integrated into a chip‐based platform that is compatible with high‐speed optical NP tracking. This system is used to investigate the lateral diffusion of 40 nm gold spheres tethered to biotinylated lipids through antibody‐functionalized ligands (single‐stranded DNA or polyethylene glycol). Although the NPs show an almost free and ergodic diffusion, their lateral motion is subject to substantial drag at the membrane surface, which leads to systematically smaller diffusion coefficients than those obtained for lipids in the membrane through fluorescence recovery after photobleaching. The lateral mobility of the NPs is influenced by the chemical composition and salt concentration at the NP‐membrane interface, but is independent of the ligand density in the membrane. Together with the observation that nanoprisms, which have a larger relative contact area with the membrane than spherical NPs, show an even slower diffusion, these findings indicate that the lateral mobility of NPs tethered in close vicinity to a membrane is significantly reduced by the friction at the NP‐membrane interface.